2019
DOI: 10.1371/journal.pone.0223237
|View full text |Cite
|
Sign up to set email alerts
|

Children’s dietary diversity and related factors in Rwanda and Burundi: A multilevel analysis using 2010 Demographic and Health Surveys

Abstract: BackgroundOne of the reported causes of high malnutrition rates in Burundi and Rwanda is children's inadequate dietary habits. The diet of children may be affected by individual characteristics and by the characteristics of the households and the communities in which they live. We used the minimum dietary diversity of children (MDD-C) indicator as a proxy of diet quality aiming at: 1) assess how much of the observed variation in MDD-C was attributed to community clustering, and 2) to identify the MDD-C associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 28 publications
5
36
2
Order By: Relevance
“…Furthermore, it is higher than the study in Kenya (6.8%) [31]. However, it is lower compared to the study conducted in Rwanda and Burundi Demographic and Health Surveys (Rwanda 23%, Burundi 16%) [32]; Tanzania [33]; Addis Ababa, Ethiopia 59.9% [34]; and Morondava (47.6%) and Moramanga (42.1%) districts of Madagascar, respectively [35].…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, it is higher than the study in Kenya (6.8%) [31]. However, it is lower compared to the study conducted in Rwanda and Burundi Demographic and Health Surveys (Rwanda 23%, Burundi 16%) [32]; Tanzania [33]; Addis Ababa, Ethiopia 59.9% [34]; and Morondava (47.6%) and Moramanga (42.1%) districts of Madagascar, respectively [35].…”
Section: Discussionmentioning
confidence: 62%
“…21,22 Earlier, it has also shown that inadequate dietary habits and feeding practices are the proximate causes of undernutrition in children. 6 According to the UNICEF, undernutrition, including underweight, stunting, and wasting, is the outcome of insufficient dietary intake and infectious diseases. 23 There were certain limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Poor feeding practices and inadequate dietary practices in infants and children, along with infectious diseases, are the causes of child undernutrition. 6,7 Moreover, feeding practices are associated with physical development, and improper feeding practices lead to poor physical development in infants and young children. 8 Consuming fewer food groups high in protein and calcium like milk products and poultry/meat may be a causing factor for child malnutrition, especially stunting.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of each group was scored "1" or "0" if otherwise. The total score ranged from 0 to 7 and was classified as adequate (≥4), and inadequate (≤3) (Custodio et al 2019). Maternal level explanatory variables included education, parity and body mass index.…”
Section: Explanatory Variablesmentioning
confidence: 99%